PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Tenriwaru Tenriwaru; Fadliah Nasaruddin (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This research aims to examine the effect of corporate social responsibility disclosure on firm value and examine the effect of profitability as a moderating variable in influencing the relationship of corporate social responsibility disclosure to firm value. The sample of this study was 13 banking companies listed on the Indonesia Stock Exchange, from 2014 to 2016, using purposive sampling techniques. The data in this study came from secondary data obtained through documentation techniques. Data analysis method used is multiple linear regression analysis. The results of this study indicate that: corporate social responsibility disclosure variable has a significant negative effect on firm value. And profitability as a moderating variable is able to strengthen the effect of corporate social responsibility disclosure on firm value.